Diversity of wasps (Hymenoptera) in alfalfa (Medicago sativa L.) farms in Basrah Governorate, Southern Iraq - Mansowr, Zainab F.; Kareem, Dhia K.; Al-Mansour, Nasir A.; Moravvej, Seyed-Abbas (Zootaxa, 2024)
Studies on the diversity of parasitoid wasps in agroecosystems exemplify the first stage of recognizing the best species to be used in biological control programs. There is an increased effort to recognize the diversity of pests in agroecosystems, but information on agricultural environments in Iraq is still unknown. This study is interested in the diversity of wasps in a cultivated area in Basrah governorate and the identification of dominant species for potential application in biological control studies. Samples were collected from alfalfa farms between January and December 2020 using two insect collection methods: sweep nets and yellow pan traps in four stations in Basrah governorate. This paper confirms that there is a high diversity of wasp species in agricultural environments. During this study, 18 wasp species were recorded for the first time in Iraq. Gronotoma micromorpha recorded the highest annual relative abundance value of 26.5%, while Chalcis biguttata recorded the lowest relative abundance of 0.89% in most agricultural environments. Numerous studies on G. micromorpha indicate that it is a parasitoid of Liriomyza species (Diptera). Thus, this species may be an important agent in the biological control of this pest.